2020
DOI: 10.3389/fpls.2020.01254
|View full text |Cite
|
Sign up to set email alerts
|

Application of Aptamers Improves CRISPR-Based Live Imaging of Plant Telomeres

Abstract: Development of live imaging techniques for providing information how chromatin is organized in living cells is pivotal to decipher the regulation of biological processes. Here, we demonstrate the improvement of a live imaging technique based on CRISPR/ Cas9. In this approach, the sgRNA scaffold is fused to RNA aptamers including MS2 and PP7. When the dead Cas9 (dCas9) is co-expressed with chimeric sgRNA, the fluorescent coat protein-tagged for MS2 and PP7 aptamers (tdMCP-FP and tdPCP-FP) are recruited to the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Several studies on epigenome editing in plants have been reviewed previously [ 151 ]. Direct fusions of dCas9 with fluorescent proteins have been used for chromosome imaging ( Figure 5 C) [ 152 , 153 , 154 ].…”
Section: Editing the Plant Genome In Transgenic Hairy Roots: Vector Componentsmentioning
confidence: 99%
“…Several studies on epigenome editing in plants have been reviewed previously [ 151 ]. Direct fusions of dCas9 with fluorescent proteins have been used for chromosome imaging ( Figure 5 C) [ 152 , 153 , 154 ].…”
Section: Editing the Plant Genome In Transgenic Hairy Roots: Vector Componentsmentioning
confidence: 99%
“…Further manipulation of the sgRNA provides the possibility of CRISPR/Casmediated targeting of different kinds of enzyme activities to specific sites in the genome. The incoporation of MS2 and other kinds of aptamers into the sgRNA for sequence-specific protein binding has been used in plants for transcriptional control, live imaging of chromosomes (Khosravi et al 2020;Lowder et al 2018), as well as for base editing. Multiplexing techniques require the simultaneous expression of multiple guide RNAs.…”
Section: Chromosomal Rearrangementmentioning
confidence: 99%
“…The authors showed that telomeres are localized in the periphery of interphase nuclei. However, in comparison with FISH, the efficiency of a telomere labeling by dCas9 was 70% [129]. To improve the labeling efficiency of CRISPR/dCas9 system, various orthologues of Sp-Cas9, including St1-Cas9 and Sa-Cas9, can be recruited in combination with modified sgRNAs with an RNA aptamer MS2/PP7 insertions that bind to a fluorescent coat protein [129].…”
Section: Other Applications Of Crispr/dcas9mentioning
confidence: 99%
“…However, in comparison with FISH, the efficiency of a telomere labeling by dCas9 was 70% [129]. To improve the labeling efficiency of CRISPR/dCas9 system, various orthologues of Sp-Cas9, including St1-Cas9 and Sa-Cas9, can be recruited in combination with modified sgRNAs with an RNA aptamer MS2/PP7 insertions that bind to a fluorescent coat protein [129]. Using this method, the dynamics of telomeres and centromeres in living plant cells can be traced.…”
Section: Other Applications Of Crispr/dcas9mentioning
confidence: 99%